Transforming Medical Students Learning: Are Pakistani Medical Institutions and Educators Prepared to Embrace Digital Technologies? - Nighat Huda (Journal of Bahria University Medical and Dental College)
Technological advancement has taken the world by storm with far reaching implications in education as well as on the learning process of students. Inspired by Ronal Harden’s recent blog1on adaptive learning that personalizes the student’s learning experience in an adaptive curriculum and talk of Khan’s Academy founder Salman Khan2 on his global success stories of promoting personalized learning through free online education, I chose to raise the issue of Pakistani medical leadership and educators’ preparedness for embracing digital technologies.